Cutting-edge advances in transethosomes and nanoethosomes for transdermal drug delivery - Prasun Patra (Discover Chemistry)
Abstract Transdermal drug delivery has long faced challenges such as poor skin permeation and low bioavailability of therapeutics. Conventional systems often fail to overcome the skin’s barrier properties, necessitating advanced vesicular carriers. Among these, transethosomes and nanoethosomes have emerged as groundbreaking solutions due to their unique ethanol-lipid hybrid structure, enabling superior drug penetration and retention. Unlike traditional liposomes, transethosomes and nanoethosomes leverage ethanol-induced membrane fluidity and nanosized deformability to enhance drug delivery. Their ability to encapsulate both hydrophilic and hydrophobic drugs with high efficiency makes them versatile for treating localized and systemic conditions. Recent studies demonstrate that these carriers significantly improve transdermal permeation, sustained release, and targeted delivery of therapeutics. Innovations in formulation techniques—such as optimizing ethanol concentration and lipid composition—have further enhanced their stability and loading capacity. Potential applications range from dermatological therapies (e.g., antifungal, anti-inflammatory) to systemic drug delivery (e.g., hormones, analgesics).Transethosomes and nanoethosomes represent a paradigm shift in transdermal delivery, addressing key limitations of conventional systems. This review synthesizes their mechanistic advantages, formulation strategies, and therapeutic potential, underscoring their role in advancing precision medicine. By bridging the gap between laboratory research and clinical applications, these nanocarriers could revolutionize treatment strategies for unmet medical needs. Graphical abstract Transethosomes and nanoethosomes based transdermal drug delivery-mechanism of action